A landscape of travel : the work of tourism in rural ethnic China / Jenny Chio. - Chio, Jenny (Studies on ethnic groups in China., 2014)
"While the number of domestic leisure travelers has increased dramatically in reform-era China, the persistent gap between urban and rural living standards attests to ongoing social, economic, and political inequalities. The state has widely touted tourism for its potential to bring wealth and modernity to rural ethnic minority communities, but the policies underlying the development of tourism obscure some complicated realities. In tourism, after all, one person's leisure is another person's labor.A Landscape of Travel investigates the contested meanings and unintended consequences of tourism for those people whose lives and livelihoods are most at stake in China's rural ethnic tourism industry: the residents of village destinations. Drawing on ethnographic research conducted in Pingan (a Zhuang village in Guangxi) and Upper Jidao (a Miao village in Guizhou), Jenny Chio analyzes the myriad challenges and possibilities confronted by villagers who are called upon to do the work of tourism. She addresses the shifting significance of migration and rural mobility, the visual politics of tourist photography, and the effects of touristic desires for "exotic difference" on village social relations. In this way, Chio illuminates the contemporary regimes of labor and leisure and the changing imagination of what it means to be rural, ethnic, and modern in China today.Jenny Chio is assistant professor of anthropology and associated faculty in film and media studies at Emory University. A Landscape of Travel is about China becoming a nation that travels, and one way of traveling is to be a tourist. Tourism is of course only one mode through which China's mobility expresses itself, and we must remember that most villages have no tourists at all. But if we want to understand why tourists see and experience what they do. and how this reflects China as a nation that travels, [this book] is both delightful and essential." - From the foreword by Stevan Harrell"This book explores how 'travel' can be a useful framework with which to better understand how rural China is changing. While it has not been uncommon to view rural China as an increasingly 'mobilized' landscape of excess labor seeking better livelihoods in the cities, Chio's study approaches mobility in both more abstract and broad-ranging terms. Her work offers an important contribution. Anyone interested in ethnography, ethnicity in China, and anthropologies of tourism will find A Landscape of Travel interesting." - Tim Oakes, University of Colorado at Boulder"--